Perilaku Bunga Pukul Delapan (Tunera ulmifolia) Akibat Perlakuan Pemotongan Daun Dan Naungan - Aries Sukariawan; Dina Arfianti Saragih; Umar Abdullah (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Sycanus is a UPDPKS predator that stays and gets food from the eight o'clock flower (Turnera ulmifolia). This study aims to determine the behavior of the eight o'clock flower due to leaf cutting and shading and its relationship with air temperature, air humidity and light intensity. This research is an experimental research, there are two treatment factors, factor 1 is leaf cutting and without cutting, factor 2 is without shading, 50% shading and 100% shading. Parameters observed were the duration of flower blooming, daily behavior of flowers, interval (duration) of flower bud blooming and weather conditions. The results showed that the eight o'clock flower without treatment experienced full bloom at 08.17 WIB and perfect bud at 13.32 WIB with a blooming duration of 4 hours 17 minutes. The process of blooming and buds takes longer in the treatment of 100% shading. Air temperature in the treatment without shade and 50% shade increased in temperature 30 minutes before the flowers bloomed and 30 minutes after the flowers experienced full bud with a maximum temperature of 35.8oC. The effect of microclimate in each treatment on blooming behavior was marked when the air temperature and light intensity increased followed by a decrease in air humidity and would bud again when the air temperature and light intensity were higher and the air humidity was lower.